Extractive colorimetric method development and validation for erlotinib in bulk and tablet dosage form - G. Usha Rani, B. Chandrasekhar, N. Devanna (Journal of Applied Pharmaceutical Science)
Two simple, rapid, sensitive, precise and economic spectrophotometric methods have been developed for the estimation of Erlotinib in bulk and tablet formulation. During the course of study, it was observed that solution of the drug formed colored ion-pair complexes with Bromocresol Green (BCG) and Methyl Orange (MO) in phosphate buffer pH 2.5, and extracted in chloroform. This property of the drug was followed for the development of colorimetric methods for analysis of drug. The complex of etoricoxib with BCG and MO showed ? max at 418.5 nm and 424.4 nm respectively. The complex was stable up to 22 hrs and obeyed Beer's law over the concentration ranges of 10-1000 µg/ml. Correlation coefficient was found to be 0.9985. In addition we have determined the molar absorptivity, Sandell sensitivity and the optimum conditions for quantitative analysis of erlotinib. These methods were validated statistically. Recovery studies gave satisfactory results indicating that none of common additives and excipients interfere the assay method. The proposed methods are found to be simple, accurate and reproducible that was successfully applied for the analysis of tablet formulation.
Keywords: Spectrophotometry, erlotinib, Bromocresol green, Methyl orange, Phosphate buffer, Ion-pair complex